A Literature Review on Central Compartment Atopic Disease as a Phenotype of Chronic Rhinosinusitis Type 2 - Muhammad Fauzi Farhat (Universitas Methodist Indonesia, 2025)
Background: Central compartment atopic disease (CCAD) is a chronic rhinosinusitis phenotype characterized by polypoid inflammatory remodeling of the middle turbinates, superior turbinates, and posterosuperior nasal septum. Recent diagnostic proposals define CCAD by central sinonasal tissue remodeling in patients displaying features of an IgE-mediated allergic response, while classifying the condition as type 2 dominant and eosinophilic. Objective: This review synthesizes current evidence regarding CCAD as a distinct phenotype in type 2 chronic rhinosinusitis, emphasizing anatomy, allergies, inflammatory endotypes, radiography, differential diagnosis, and therapeutic implications. Methods: A narrative literature review was conducted using articles from 2016 to 2026 published in Scopus-indexed peer-reviewed journals. Results: Current studies demonstrate a significant association between CCAD and inhalant allergy or aeroallergen sensitization, although the strength of the relationship between systemic allergy and asthma varies among populations. Eosinophilia and a cytokine profile marked by IL-5 and IL-13 in central compartment chronic rhinosinusitis confirm type 2 characteristics. Conclusion: CCAD should be considered an anatomically oriented, allergy-related manifestation of chronic rhinosinusitis type 2, rather than simply a diffuse nasal polyp. Keywords: endoscopic sinus surgery, type 2 inflammation, nasal polyps, chronic rhinosinusitis, and allergic rhinitis.